Decision Support System Legalization Of Distribution Substation With Priority Weighting Bayes Method - Andryas Yuli Anggoro; Bandi Bandi (Journal Of Social Science (JoSS), 2024)
PT PLN Batam is a national company operating in the field of electricity in the Batam region. As of December 2023, the number of customers is 367,709. Electricity consumption on Batam Island continues to increase with an average annual growth of 6.39% (2013-2023), and the average customer growth is 4.07% per year (2013-2023). This growth is accompanied by an increase in the assets of electricity distribution equipment, especially distribution substations. Distribution substations in PT PLN Batam consist of two types: concrete distribution substations and portal distribution substations. The total number of distribution substations as of December 2023 is 1,849. Distribution substations are vital distribution assets, requiring proper handling, especially regarding legal ownership of the land occupied by the substations. Land issues primarily occur in locations where distribution substations are situated in business centers or along main road medians. With the continuous increase in distribution substations, land legalization issues also escalate. To mitigate the risk of these land issues, PT PLN Batam implements the Decision Support System for the Legalization of Distribution Substations with Priority Weighting Bayes Method. This method, a qualitative approach, involves ranking distribution substations based on the highest to lowest risk. The goal of implementing the Bayes method is for the company to prioritize which distribution substations need to be legalized first and minimize land dispute issues in the future.